Considérations sur le rapport n/p dans les eaux marines du littoral roumain de la Mer Noire - Voinescu, Iulia; Cociașu, Adriana; Dorogan, Liliana (Cercetări Marine - Recherches Marines, 2026)
The paper presents some considerations on N/P ratio in Danube water at Sulina and sea water from the littoral zone of Constantza and Mangalia and also in limits of 30 Mm East from Constantsa (0-50 m depth). The authors corelate the seasonal variations with anthropic influences and biological cycle of phytoplankton.